Late onset of Guillain-Barré syndrome following SARS-CoV-2 infection: part of 'long COVID-19 syndrome'?. Issue 1 (18th January 2021) - Raahimi, Mina M; Kane, Alice; Moore, Christopher EG; Alareed, Ahmad W
Abstract : We describe a case of delayed onset, acute demyelinating neuropathy secondary to novel SARS-CoV-2 infection. A previously healthy 46-year-old man presented with bilateral leg pain and loss of sensation in his feet 53 days after having COVID-19 pneumonitis. He developed painful sensory symptoms followed by a rapidly progressive lower motor neuron weakness involving all limbs, face and respiratory muscles, needing ventilatory support. In keeping with a diagnosis of Guillain-Barré syndrome, cerebrospinal fluid examination showed albuminocytologic dissociation and nerve conduction studies supported the diagnosis of an acute inflammatory demyelinating polyradiculoneuropathy. The delayed neurological dysfunction seen in our patient following SARS-CoV-2 infection may indicate a novel mechanism of disease that is part of the emerging 'long COVID-19 syndrome'.